Estimating of Survival Function of Hepatitis Virus in Jember - Mohamad Fatekurohman (Jurnal ILMU DASAR, 2007)
Statistical method to analyse data of lifetime is called survival analysis. One problem in survival analysis is estimation of survival function. This function can be estimated by using nonparametric method. One problem in  medical is to study the lifetime of hepatitis virus. In this paper the lifetime of hepatitis viruses (A, B, C) are estimated using Nelson’s method. The results show that the three type of viruses have different lifetime and virus type A has the longest lifetime.